Fluxo de biomassa, produção de forragem e composição quimico-bromatológica do capim-mombaça sob adubação e irrigação - Mochel Filho, William de Jesus Ericeira (2009)
This work was carried out to evaluate the effects of different irrigation levels and rates of nitrogen on the morphogenetic and structural characteristics, yield production and the composition chemical-bromatologic of mombaçagrass (Panicum maximum cv. Mombaça). The study was conducted in the period from August to December 2007 on Unit Research of EMBRAPA MEIO NORTE, located in city of Parnaíba, Piauí. The treatments consisted of four doses of nitrogen (200, 400, 600 and 800 kg N/ha x year) and two irrigation levels (with a equivalent level to replacement of 50% and 80% of evaporation of the Class A pan - ECA), in a completely randomized block design in a 4 x 2 factorial design with three replications. The plots measuring 3 x 8 m, with 2 x 7 m as floor area for data collection, and made a cut of uniformity (in August) and four cuts to collect data every 30 days (September, October, November, December) 20 cm above the soil. The irrigation level of 80% increases the values of leaf appearance rate (LAR), leaf elongation rate (LER), culm elongation rate (CER) and final leaf length (FLL) when compared with the blade of 50%. Nitrogen fertilization did not influence the LAR, LER, leaf senescence rate (LSR), duration of life of the leaf (DLF) and the FLL. However, with increasing doses of N are the highest values of CER and the lowest dose of N implies a higher value for number of live leaves per tillers (NLT). With the increase of nitrogen rates were increased total dry matter yield (PMST), dry matter yield of green blade (PMSLV), dry matter yield of green culm (PMSCV) and the height of plants and a reduction in nitrogen use efficiency (NUE). The irrigation levels affected only height of grass when the layer of 80% has higher values. Increasing doses of nitrogen reduces the dry matter at the same time as the irrigation level of 80% decreasing these values, both for the leaf and to stem+sheath fraction. With increasing doses of nitrogen there is an increase in levels of neutral detergent insoluble fiber (NDF) and acid detergent insoluble fiber (ADF) only in the leaf and crude protein (CP), both for the leaf and to stem+sheath fraction. The irrigation level of 80% decreases the CP levels, both for the leaf and to stem+sheath fraction at the same time it increases the levels of ADF both for the leaf and to stem+sheath fraction. In the conditions which this work has been done it is recommended to use the blade of 50% of irrigation with nitrogen fertilization between 600 and 800 kg N/ha x year